Infant and toddler teachers' professional development : reported changes in perceptions and practice : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Education in Early Years, Massey University - Bary, Raewyne (Massey University, 2009)
The aim of this study was to explore any changes in perceptions and/or practice of a group of infant and toddler teachers as a result of their participation in a facilitated professional development programme. This professional development programme and a teaching team which was committed to implementing an Attachment Based Learning programme (ABL) already imbedded in another section of their centre, held the potential for identifying changes in teachers' practices in response to their increased understandings of the theories, philosophies and beliefs underpinning the ABL programme. The experiences of two focus teachers, two professional development facilitators and five infant and toddler teachers' involvement in a centre specific co-constructed professional development programme along with two parent users of the centre are documented in this report using a qualitative mixed-method approach. Data were generated with participants for the duration of the professional development programme spanning a seven month time frame. The teachers were interviewed twice; once at the beginning of the programme and then at the completion of the programme. The parents were interviewed once on the completion of the professional development programme. Data from the interviews as well as teachers' reflective journals, meeting minutes and centre policies were analysed qualitatively using Rogoff's (2003) three planes of analysis; the personal, the interpersonal and the institutional planes. From these planes three thematic categories were revealed in which teachers' understandings were concentrated. These themes were the teachers' view of the child as informant to their practice; how they perceived their role as a teacher; and the importance of team cohesion. Changes in teachers' practice within these three areas were examined, as were the professional development processes that influenced the teachers' perception and pedagogy. The study showed that there needs to be alignment of these concepts across and within the three planes to ensure optimal outcomes for all participants in the learning community. This study has emphasized how professional development can shape teachers' views, understandings and pedagogy. The study contributes to an understanding of the importance of teachers having opportunities to theorise practice, and undertaking authentic and contextual professional development within safe and trusting environments.
Keywords: New Zealand; Early childhood teachers -- In-service training; Attitudes